1976
DOI: 10.2337/diab.25.3.223
|View full text |Cite|
|
Sign up to set email alerts
|

Peripheral T-lymphocytes in Juvenile-onset Diabetics (JOD) and in Maternity-onset Diabetics (MOD)

Abstract: The percentage and absolute number per mm.3 of peripheral T-lymphocytes were determined in 11 juvenile-onset diabetics (JOD), in 21 maturity-onset diabetics (MOD), and in 18 normal subjects (NS). The percentage was significantly lower in JOD (38.1) than in MOD (57.2) and NS (56.5). The absolute T-lymphocytes number per mm.3 was significantly lower in JOD (833) than in NS (1,260); this was also true for JOD as against MOD (1,026), even if the difference was not statistically significant. No difference was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

1977
1977
1986
1986

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 5 publications
1
8
0
1
Order By: Relevance
“…The data presented show a significant reduction of peripheral T-lymphocyte percentage in insulin dependent diabetics. These results agree with previous reports from this laboratory [9,11] and with findings from other authors [10,12,13], but differ from Lymphocyte E-rosetting % Basal (11) 57.9 _+ 3.6 Glucose 100 mg/100ml (11) 51.0 _+ 3.2 NS Glucose 300 mg/100ml (11) 50.5 _+ 3.2 NS Glucose 500 rag/100 ml (10) 51.1 _+ 3.9 NS NS = not significant those of MacCuish et al [14] and Hann et al [22]. The discrepancies may be due both to difference in methods and to heterogeneity among the examined patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The data presented show a significant reduction of peripheral T-lymphocyte percentage in insulin dependent diabetics. These results agree with previous reports from this laboratory [9,11] and with findings from other authors [10,12,13], but differ from Lymphocyte E-rosetting % Basal (11) 57.9 _+ 3.6 Glucose 100 mg/100ml (11) 51.0 _+ 3.2 NS Glucose 300 mg/100ml (11) 50.5 _+ 3.2 NS Glucose 500 rag/100 ml (10) 51.1 _+ 3.9 NS NS = not significant those of MacCuish et al [14] and Hann et al [22]. The discrepancies may be due both to difference in methods and to heterogeneity among the examined patients.…”
Section: Discussionsupporting
confidence: 94%
“…As to cell mediated immunity, there are reports of T-cell defects, manifested by low counts of Erosette forming cells [9,10,11,12,13] and impaired in vitro response to T-cell mitogens [14,15].…”
mentioning
confidence: 99%
“…Cell-mediated immunity like heredity, virus infections [1] and humoral immunity [2] may play an important role in the aetiology of diabetes [3][4][5][6]. Studies on circulating lymphocytes in diabetics have given variable results [7][8][9][10][11][12][13] which may be due to differences in methodology, selection of patients or metabolic control at the time of the study. In order to re-examine these findings, we have studied circulating lymphocyte subpopulations in the juvenile insulin dependent type of diabetes which may be related aetiologically to immunological factors [14,15].…”
mentioning
confidence: 99%
“…An alternate possibility is that a virus might produce a low-grade persistent or non-lyric infection of beta, cells ~nd that destruction of the infected beta cells is due to the immune response of the host. Others demonstrated that antigens from pancreatic tissue inhibited to a markedly greater extent the migration of leukocytes from insulin-dependent diabetics than from controls (46, 57--59, 69) and in one study, it ws~s reported that the percentage of peripheral T lymphoeytes was decreased in patients with juvenile-onset as compared to maturity-onset diabetes (9). Recently, however, investigators from several laboratories found that diabetic patients respond immunologically to pancreatic tissue.…”
Section: Genetic and Immunologic Factorsmentioning
confidence: 99%